Hey!
-------------------------------------------------
Since we know that both expressions lay on a straight line, we know that when both lines add up it should be 180°
-------------------------------------------------
We can write the expression as (7x - 1) + (6x - 1) = 180
-------------------------------------------------
Simplify
→ (7x + −1) + (6x + −1) = 180
Combine Like Terms
→ (7x + 6x) + (-1 + -1) = 180 → 13 + -2 = 180
Add 2 To Both Sides
→ 13x - 2 + 2 = 180 + 2 → 13x = 182
Divide 13 To Both Sides
13x/13 = 182/13 → x = 14
-------------------------------------------------
Hence, the value of x is 14!
-------------------------------------------------
Hope This Helped! Good Luck!